DIGITAL FATIGUE: A CASE STUDY OF CULINARY ARTS STUDENTS ON THE ONLINE DISTANCE LEARNING (ODL) DURING PANDEMIC-19 - Norfezah Md Nor; Nur Sabrina Abdul Razak; Mohd Syafiq Othman (Journal of Islamic, Social, Economics and Development, 2022)
The pandemic shifted universities teaching and learning from in-person to onlinedistance learning (ODL) in an instant, including the Culinary Arts students, UniversitiTeknologi MARA Cawangan Pulau Pinang they were not exempted from this adjustment. Thisabrupt transition has disrupted their learning process and triggered a plethora of concerns,which is a digital fatigue. Therefore, this study aimed to identify causes towards the digitalfatigue faced by culinary students in UiTM Cawangan Pulau Pinang during ODL classes. Aqualitative research approach was employed with a total of eleven (11) students wereinterviewed using a semi-structured interview questions. The findings revealed that there werenine (9) factors contributed towards digital fatigue with five main factors influenced the most;technology issue, academic overload, screen time, sedentary behaviour and time management.Early identification causes of digital fatigue may help to mitigate the issues.